Cryo-EM structure of islet amyloid polypeptide fibrils reveals similarities with amyloid-β fibrils - Röder, Christine; Kupreichyk, Tatsiana; Gremer, Lothar; Schäfer, Luisa U.; Pothula, Karunakar R.; Ravelli, Raimond B. G.; Willbold, Dieter; Hoyer, Wolfgang; Schröder, Gunnar F. (Nature Structural & Molecular Biology, 2020)
Amyloid deposits consisting of fibrillar islet amyloid polypeptide (IAPP) in pancreatic islets are associated with beta-cell loss and have been implicated in type 2 diabetes (T2D). Here, we applied cryo-EM to reconstruct densities of three dominant IAPP fibril polymorphs, formed in vitro from synthetic human IAPP. An atomic model of the main polymorph, built from a density map of 4.2-Å resolution, reveals two S-shaped, intertwined protofilaments. The segment 21-NNFGAIL-27, essential for IAPP amyloidogenicity, forms the protofilament interface together with Tyr37 and the amidated C terminus. The S-fold resembles polymorphs of Alzheimer's disease (AD)-associated amyloid-β (Aβ) fibrils, which might account for the epidemiological link between T2D and AD and reports on IAPP-Aβ cross-seeding in vivo. The results structurally link the early-onset T2D IAPP genetic polymorphism (encoding Ser20Gly) with the AD Arctic mutation (Glu22Gly) of Aβ and support the design of inhibitors and imaging probes for IAPP fibrils.